Development of e-Modules for Physical Education, Sports and Health Education on Football Materials Based on Playing Football for Elementary School Students - Febrian Hidayat; Kamal Firdaus; Arsil Arsil; Roma Irawan (JETL (Journal of Education, Teaching and Learning), 2025)
The problem in the research is in the background because the understanding of the football game of Shiva Sd Bakti 2 nairatul jannah has not been maximized. This is suspected, because the learning process given to students does not run well for the understanding of elementary school students. The purpose of the research is to develop physical education teaching materials E-Module for Physical Education, Sports and Health on Football Materials Based on Playing Football for elementary school students. The research model used is Research and Development (R&D) with the Borg and Gall approach modified by Sugiyono. The research method used is Research and Development (R&D) with a modified development model from Borg & Gall. The research stages include problem identification, data collection, e-module design, expert validation, product trials, and revision and refinement. The subject of the study was a student of SD IT Bakti 2 Nairatul Jannah, who showed high enthusiasm for the game of football but had difficulty in understanding the game strategy effectively. The validation results show that the e-module developed meets the eligibility criteria with the category of "very feasible" to be used in PJOK learning. In addition, field trials showed an increase in students' understanding of basic football techniques, game strategies, as well as increased motivation to learn. Thus, this e-module is expected to be an innovative solution in increasing the effectiveness of PJOK learning in elementary schools.